Pendugaan Cadangan Karbon Permodelan Penerapan Penanaman Asam jawa pada Jalur Hijau Jalan-jalan Tol Semarang-Solo - Abdillah Rangga Fajar; Rifandi Raditya Ahmad (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2019)
The increasing length of toll roads on the island of Java also increases the number of green lane that can be used for greening. One of the functions of the green road is for planting carbon-absorbing plants. Tamarind (Tamarindus indica) trees are a type of productive plants that have a carbon sink function. The purpose of this study is to estimate the carbon stock of a model of planting on the green lane of the Semarang-Solo toll road. This research was conducted in September 2019. The method used in this study is simulation calculation and allometric models. Calculation simulation method is used to determine the potential availability of land along the green lane of the Semarang-Solo toll road. Carbon reserve calculation method is done by nondestructive sampling by using an allometric model for the tamarind tree species. The application of this model can produce estimates of stored carbon stock approximately 197.165 ton. Green lane has a very large utilization potential for carbon sequestration and should be used optimally.